THE CONSEQUENCES OF URBAN AIR POLLUTION FOR CHILD HEALTH: WHAT DOES SELF-REPORTING DATA IN THE JAKARTA METROPOLITAN AREA REVEAL? - Mia Amalia; P Resosudarmo; Jeff Bennet (Masyarakat Indonesia, 2013)
Since the early 1990s, the air pollution level in the Jakarta Metropolitan Area hasarguably been one of the highest in developing countries. This article utilizes selfreporting data on illnesses available in the 2004 National Socio-Economic HouseholdSurvey to test the hypothesis that air pollution impacts human health, particularlyamong children. Test results confirm that air pollution, represented by the PM10 levelin a sub-district, significantly correlates with the level of human health problems,represented by the number of restricted activity days (RAD) in the previous month.Results show that the younger the person, the higher the number of RAD in theprevious month; that is the impact of a given level of PM10 concentration is morehazardous for children.Keywords: Air pollution, Environmental economics, Health economics, Exposureresponse model